Revisiting the Significance of ZDP and Scaffolding in English Language Teaching - Muntasir, Muntasir; Akbar, Indra (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2023)
This study aims to describe the definition and application of ZPD and scaffolding in English language instruction. This study is a critical review that focuses on how ZPD and scaffolding can be used to construct and structure curriculum materials. Scholars and practitioners in the field of language learning have always sought to develop a theory to facilitate the learning process for students. Some academics have focused on ways to improve students' performance in language learning or how teachers might facilitate the language-learning process. To genuinely know what to help with and how to aid, language teachers must be aware of their students' capacities. The instructor should view students as distinctive individuals with distinct needs, identities, and skills. Teachers should recognize what children can perform alone and what they need assistance with. To empower the teacher, Vygotsky (1978) proposed the Zone of Proximal Development (ZPD) and Scaffolding theories. In this study, we endeavor to examine the theory of ZPD and Scaffolding. Secondly, we apply this idea to the context of language teaching and learning. Lastly, we discuss the significance of these theories for language learner identity.